STUDENTS’ PERCEPTION TOWARD ENGLISH ONE FOR TWENTY PROGRAM (EOT) IN UNIVERSITAS ISLAM MALANG - Raka Wahyu Prayoga (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This article gives an overview of a piece of qualitative research conducted at University of Islam Malang. This paper present an attempt to describe students’ perception on EOT program, to look tutees’ perception being taught by peer tutor and to know tutor teaching’s strategy on learning. Five tutors and five tutees in different peer tutoring group were involved. The findings revealed that tutees are comfortable and happy being taught by tutor. Tutors outlined that searching for resources and preparing the materials before teaching, using games as a learning tool, giving different approach are the strategies to help tutees on learning. EOT program provides an effective program to improve English skill and it is valuable to develop teaching skill for tutor. However, time management and incomplete facility are the barriers for tutor and tutee during learning process.Key words: EOT program, peer tutoring, learning English